1988
DOI: 10.1111/j.1939-0025.1988.tb01579.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of behavior in adolescent rape.

Abstract: A study of 67 rapes by 63 California adolescents has yielded a highly representative composite picture of the typical rape episode by a juvenile assailant. Previously unexplored behavior patterns have emerged, including prior drug use, impulsivity, and lack of victim provocation. These findings have practical implications for clinicians treating rape victims and for the rehabilitation of adolescent rapists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
2
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 21 publications
5
19
2
2
Order By: Relevance
“…On average, 50% of convicted rapists consumed alcohol at the time of the assault; a rate that is comparable to that for other violent crimes (Coid, 1986;Collins & Messerschmidt, 1993;Johnson, Gibson, & Linden, 1978;Rada, 1975;Scully, 1991;Vinogradov, Dishotsky, Doty, & Tinklenberg, 1988). Similarly, in Ageton's (1983) survey of adolescent community sexual assault perpetrators, approximately half of the offenders were drinking prior to the assault.…”
Section: The Prevalence Of Alcohol-involved Sexual Assaultmentioning
confidence: 91%
“…On average, 50% of convicted rapists consumed alcohol at the time of the assault; a rate that is comparable to that for other violent crimes (Coid, 1986;Collins & Messerschmidt, 1993;Johnson, Gibson, & Linden, 1978;Rada, 1975;Scully, 1991;Vinogradov, Dishotsky, Doty, & Tinklenberg, 1988). Similarly, in Ageton's (1983) survey of adolescent community sexual assault perpetrators, approximately half of the offenders were drinking prior to the assault.…”
Section: The Prevalence Of Alcohol-involved Sexual Assaultmentioning
confidence: 91%
“…One study found that individuals with lower SES are more likely to be victims as well as perpetrators of sexual violence (Vinogradov, Dishotsky, Doty, & Tinkenberg, 1988). Other studies that examined father's occupation and income as an indicator of SES have shown no effects on rape myth acceptance (Feltey, Ainslie, & Geib, 1991;Gray, Palileo, & Johnson, 1993).…”
Section: Journal Of Youth Development Bridging Research and Practicementioning
confidence: 99%
“…Lorsque ce fut le cas, les auteurs ont choisi de les comparer, par exemple, sur la base de leur réponse à une épreuve psycho-métrique (Kempton et Forehand, 1991 ;Smith, Monastersky et Deisher, 1987), sur celle du type de délit commis (Becker, Cunningham-Rathner et Kaplan, 1987), ou sur celle des caractéristiques de l'agression (Vinogradov, Dishotsky, Doty et Tinklenberg, 1988).…”
Section: Problématiqueunclassified
“…Les deux groupes se démarquent de façon statistiquement significative (p = 0,001) quant à cette dernière variable, les agresseurs contre les femmes montrant une plus forte tendance (29 % vs 0%) à être intoxiqués au moment du délit. C'est une différence qui a aussi été notée à plusieurs reprises chez les délinquants sexuels adultes (Quinsey, 1984(Quinsey, , 1986Aubut et McKibben, 1985) et chez les adolescents (Vinogradov et al, 1988).…”
Section: Délitunclassified